Review on inhibition mechanism of tea polyphenols against tumor immune escape - KONG Dedong; ZHAO Yueling; WANG Yuefei; XU Ping (浙江大学学报. 农业与生命科学版)
Tea polyphenols (TP) are the main active compounds in tea leaves. It is found that TP could inhibit cancer cell growth and induce cell apoptosis via modulating cell cycle, gene expression, signal transduction and transcription factor, etc. However, due to the low bioavailability of TP, it is hard for TP to work on cancer cells directly, which leading to the anti-tumor mechanism effect of TP is still unclear. As known, tumor immune escape is found to play a key role in tumor genesis and growth; immunosuppressive cells, such as myeloid-derived suppressor cells (MDSCs), are able to regulate anti-tumor immune response negatively, and mainly contribute to tumor immune escape. Recently, TP have been found to relieve immune escape and suppress spontaneous neuroblastoma cells through MDSCs, which provide a new sight into understanding the anti-tumor effect of TP. In this paper, the recent researches on the effects of tea polyphenols on immunosuppressive cells were reviewed in order to provide a reference for studying the anti-tumor mechanisms of tea polyphenols.